2013
DOI: 10.1093/carcin/bgt206
|View full text |Cite
|
Sign up to set email alerts
|

miR-451 inhibits cell proliferation in human hepatocellular carcinoma through direct suppression of IKK-β

Abstract: It has been demonstrated that nuclear factor-kappa B (NF-κB), which is overactivated in hepatocellular carcinoma (HCC), plays important roles in the development of HCC. Recently, a group of dysregulated micro RNAs were reported to be involved in HCC progression. Further understanding of micro RNA-mediated regulation of NF-κB pathway may provide novel therapeutic targets for HCC. In this study, we found that miR-451 expression was markedly downregulated in HCC cells and tissues compared with immortalized normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 49 publications
3
58
1
Order By: Relevance
“…These findings suggested that miR-451 plays an important role in the pathophysiological mechanisms involved the progression of NAFLD. Previously, many research groups have also demonstrated different biological functions for miR-451 in carcinogenesis and tumor progression by affecting cell proliferation, cell-cycle distribution, migration, and invasion (Bergamaschi and Katzenellenbogen, 2012;Gal et al, 2008;Li et al, 2013;Liu et al, 2013;Tian et al, 2012). In this study, we identified miR-451 as a NAFLD-expressed miRNA that regulates the production of inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggested that miR-451 plays an important role in the pathophysiological mechanisms involved the progression of NAFLD. Previously, many research groups have also demonstrated different biological functions for miR-451 in carcinogenesis and tumor progression by affecting cell proliferation, cell-cycle distribution, migration, and invasion (Bergamaschi and Katzenellenbogen, 2012;Gal et al, 2008;Li et al, 2013;Liu et al, 2013;Tian et al, 2012). In this study, we identified miR-451 as a NAFLD-expressed miRNA that regulates the production of inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…miR-451 is known to exert various biological functions in cancer, infectious disease, cardiovascular and metabolic diseases. Previous studies have revealed that the dysregulation of miR-451 expression is involved in carcinogenesis and in tumor progression by affecting cell proliferation, cell-cycle distribution, migration, and invasion (Li et al, 2013;Liu et al, 2013;Tian et al, 2012). Furthermore, a recent study showed that miR-451 regulates dendritic cell cytokines and suppresses neutrophil chemotaxis via downregulation of p38 MAPK phosphorylation (Murata et al, 2014;Rosenberger et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that deregulation of “oncomirs” miR‐21, miR‐155, miR‐192 and tumour suppressor miR‐375, miR‐451a and miR‐34a is associated with laryngopharyngeal cancer 12, 13, 14, 15, 16, 17. Moreover, an independent association has been demonstrated between NF‐κB activation and up‐regulation of oncogenic miR‐21 and/or down‐regulation of tumour suppressor miR‐34a and miR‐451a 21, 22, 23…”
Section: Introductionmentioning
confidence: 99%
“…The band intensity obtained in control cells ''C'' was set as 1, and the relative fold change was determined and shown as the mean AE the standard deviation of at least three independent experiments. ****p < 0.0001, ***p < 0.001, **p < 0.01, and *p < 0.05. inhibition of miR-451 was assessed in K562 cells by analyzing proteins whose mRNAs are targeted by miR-451 (Bcl2, AKT, and c-myc) [24][25][26][27]. All target proteins were overexpressed in 451-Inh transfected control cells, while VPA-mediated down-regulation of the GATA-1/miR-144/451 axis impacted AKT and Bcl2 proteins but not c-myc.…”
Section: Discussionmentioning
confidence: 99%
“…Mature miR-144 and miR-451 are specifically expressed in erythroid cells [21,23], and increased miR-451 expression is associated with a significant decrease in AKT and Bcl-2 expression [24,25]. Moreover, c-myc expression is repressed by miR-451 in correlation with predicted targeting of c-myc mRNA by miR-451 [26,27]. Moreover, PU.1 and ETS-1 have been described as targets of miR-155 [28,29], while RUNX1 regulates transcription of the miR-221/222 and miR-27a genes [30,31].…”
Section: Introductionmentioning
confidence: 99%